Triclocarban at environmentally relevant concentrations induces the endoplasmic reticulum stress in zebrafish. Issue 3 (28th December 2018) - Zhou, Ting; Wei, Jiajing; Su, Yufang; Hu, Zhiyong; Li, Ying; Yuan, Hongfang; Zhao, Kai; Liu, Chunyan; Zhang, Huiping
Abstract: Triclocarban (TCC) is an antibacterial agent commonly found in environmental, wildlife, and human samples. However, with in‐depth study of TCC, its negative effects are increasingly presented. Toxicological studies of TCC at environmentally relevant concentrations have been conducted in zebrafish embryos and indicated that TCC leads to deformity of development causes developmental deformities. However, the molecular mechanisms underlying the toxicity of TCC in zebrafish embryos have not been entirely elucidated. We investigated whether exposure to TCC at environmentally relevant concentrations induces endoplasmic reticulum (ER) stress and unfolded protein response (UPR) in zebrafish. Zebrafish embryos were grown to 32 hours post fertilization and exposed to 2.5, 5, and 10 μg/L TCC and used in whole‐mount in situ hybridization to visualize the expression of ER chaperone hspa5 and ER stress‐related apoptosis factor chop . Zebrafish livers were exposed to different concentrations of TCC to elaborate the relationships between fatty degeneration and ER stress. Then, a human hepatic cell line (HL‐7702) was used to test whether TCC induced ER stress in human livers similar to those of zebrafish. In zebrafish embryos, TCC induced high hspa5 expression, which could defend against external stimulations. Furthermore, hapa5, hsp90b1, and chop exhibited ectopic expressions in the neuromast, intestinal tract, and tail tip of zebrafish embryos. On the one hand, significant differences were observed in the mRNA and protein expressions of the ER stress molecular chaperone pPERK‐pEIF2a‐ATF4 and ATF6 pathways in HL‐7702 cells exposed to TCC. On the other hand, lipid droplet accumulation slightly increased in zebrafish livers exposed to 10 μg/L TCC in vitro. These results demonstrate that TCC not only damages the development of zebrafish embryos and structure of zebrafish liver but also influences human hepatic cells by activating ER stress and the UPR signaling pathway.